Effect of nanostructured ferrites MFe2O4 (M= Cu, Co, Mg, Zn) on the thermal decomposition of ammonium nitrate - Cabrera, Alejandra Fabiana (2021)
Ammonium nitrate (NH4NO3) represents a cheap, chlorine-free alternative to ammonium perchlorate for use as an oxidant for solid propellants. But its poor ignitability and low burning rate are all disadvantages to achieve such purposes. For this reason, it is necessary to carry out studies to improve its combustion characteristics, seeking to combine it with catalysts or fuels. The present work explores the possibility of improving its combustion characteristics by adding ferrites as catalysts. Nanostructured ferrites MFe2O4 (M= Mg, Co, Cu, and Zn) synthesized by autocombustion method were tested as catalysts for the thermal decomposition reaction of ammonium nitrate under open, partially open or sealed conditions. The ferrites were characterized by XRD, SEM, UV-vis spectrophotometry and Mössbauer spectroscopy. All the MFe2O4 samples are single phased with a cubic spinel structure and average sizes, L, ranging from about 9 (CoFe2O4) to 25 nm (CuFe2O4). The catalytic effect of MFe2O4 on the thermal decomposition of NH4NO3 was investigated by thermogravimetric analysis and differential scanning calorimetry techniques. The process was also followed in a volumetric Sieverts type apparatus. The results indicate that only under sealed conditions the addition of these ferrites has influence in the decomposition process of AN. The incorporation of any of these ferrites decreases the onset temperature of the process manifested itself through an exothermic reaction, and also increases the amount of heat released in the reaction. The Co-ferrite showed the best efficiency causing the onset temperature to drop around 60 °C. The catalytic performance is correlated with the electronegativity of M2+ cations, which act as Lewis acid sites that interact with the gas molecules.